The Importance of Soil Health for Residential Landscapes - Sally Scalera; A. J. Reisinger; Mary Lusk (EDIS)
This 6-page publication’s purpose is to educate master gardeners and homeowners about the principles of soil health as well as practices that harm or nurture soil health at the residential scale. It also includes a description of the soil food web and the microorganisms that comprise it. This new publication of the UF/IFAS Department of Soil and Water Sciences was written by Sally Scalera, Alexander J. Reisinger, and Mary Lusk. http://edis.ifas.ufl.edu/ss664